Localized surface plasmon-enhanced photoluminescence of amorphous silicon quantum dots through plasmonic subwavelength crossed metallic gratings. (29th March 2016) - Tsai, Tsung-Han; Lin, Ming-Yi; Hsiao, Li-Jen; Choi, Wing-Kit; Lin, Hoang Yan
Abstract: We investigate experimentally the enhancing effect of plasmonic subwavelength crossed Ag gratings on photoluminescence (PL) from the amorphous silicon quantum dots (a-Si QDs) embedded in a central silicon-rich SiO x film of the Ag/SiO x :a-Si QDs/Ag sandwich nanostructures. The use of the crossed Ag grating structure as the top layer in the sandwich nanostructures results in a 2-fold increase in the PL peak intensity and a 1.34-fold increase in the integrated emission intensity compared with the use of a one-dimensional (1D) Ag grating top layer, and a 1.53-fold peak intensity increase compared with that of a SiO x :a-Si QDs/Ag structure without a Ag top layer. These significant PL enhancements can be attributed to the high light-extraction efficiency of the polarization-independent crossed metallic grating structure, the strong out-coupling of localized surface plasmons (LSPs), and the strong a-Si QD–LSP coupling.